Rio +20, Rio de Janeiro - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
On June 21, the Danish government hosted a side event at Rio+20 titled "Sustainable, Incluive Growth: The Way Forward from Rio+20 and G20". The aim of the session was to address the challenge of speed-to-scale in securing green and inclusive growth called for by the Secretary-General's High Level Panel on Global Sustainability, and explore how platforms such as the Global Green Growth Forum can contribute to spur action and scale up and intensify business contribution in the transition to a green economy. The program featured keynote speeches and a high-level panel discussion.